The Role of Arabic Education Department in Improving Students' Writing Skills During Covid-19 Pandemic - Nurbayan, Yayan; Al Farisi, Mohamad Zaka; Sanusi, Anwar; Supriadi, Rinaldi (LISANIA: Journal of Arabic Education and Literature, 2021)
Writing skills are definitely essential to be mastered by students. This study described the efforts of Arabic education department of Indonesia University of Education (IUOE) in improving students’ writing skill, specifically in writing journal articles. Descriptive qualitative method was used in this study. This study involved 25 postgraduate students. Data collection was carried out through questionnaires, interviews, and documentation. The results of this study showed there are four stages that can be performed to improve students’ writing skill in writing journal article, namely 1) Identifying students’ various difficulties in writing scientific journal articles, 2) conducting trainings of scientific journal articles through zoom meeting application in which the materials are based on the problems faced by the postgraduate students, 3) evaluating scientific journal articles that have been written by the postgraduate students, and 4) knowing the students’ perceptions regarding scientific journal article training activities through distributing the questionnaires.